A review on prolificacy genes in sheep - Abdoli, R; Zamani, P; Mirhoseini, SZ; Ghavi Hossein-Zadeh, N; Nadri, S (Reproduction in domestic animals, 2016)
Contents Ovulation rate and litter size are important reproduction traits in sheep and are of high economic value. Reproduction traits typically have low to medium heritabilities and do not exhibit a noticeable response to phenotypic selection. Therefore, inclusion of genetic information of the genes associated with reproductive ability could efficiently enhance the selection response. The most important major genes affecting prolificacy and their genetic diversities in different sheep breeds were reviewed. Different causative mutations with major effects on reproductive traits including ovulation rate and litter size have been found in various sheep breeds around the world. A general overview of the studies on main prolificacy genes showed that some alleles may express different phenotypic effects in different breeds, and thus, further studies on epistatic effects are necessary for more understanding of genetic control of reproductivity in sheep. Regarding the polygenic control of fertility traits, application of new high‐throughput technologies to find new variants is essential for future studies. Moreover, genomewide association studies and genomic best linear unbiased predictions of breeding values are likely to be effective tools for genetic improvement of sheep reproductive performance traits.